Experimental Researches on Long-Term Strength of Granite Gneiss - Lin Liu; Weiya Xu (Advances in Materials Science and Engineering)
It is important to confirm the long-term strength of rock materials for the purpose of evaluating the long-term stability of rock engineering. In this study, a series of triaxial creep tests were conducted on granite gneiss under different pore pressures. Based on the test data, we proposed two new quantitative methods, tangent method and intersection method, to confirm the long-term strength of rock. Meanwhile, the isochronous stress-strain curve method was adopted to make sure of the accuracy and operability of the two new methods. It is concluded that the new methods are suitable for the study of the long-term strength of rock. The effect of pore pressure on the long-term strength of rock in triaxial creep tests is also discussed.